The Impact of the Window Shopping Learning Model on Learning Outcomes of Junior High School Students - Effendi, Muhammad Yusuf; Widiyatmoko, Wahyu (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2023)
This study aims to analyze the effect of window shopping learning model on the learning outcomes of seventh-grade students in social studies subjects. This research is quasi-experiment research with a randomized pretest-posttest control-group design. Determination of the sample in this study using a simple random sampling technique with the results of the draw obtained class VII B as an experimental class and class VII E as a control class consisting of 30 students each. The results showed that of hypothesis testing which obtained the value of Sig. (2-tailed) <0.05, it is concluded that the window shopping learning model can affect the learning outcomes of junior high school students in Class VII in social studies subjects with the material of the condition of the territory of Indonesia. The results of this study contribute to identifying effective learning approaches for junior high school level, particularly in social studies, and provide valuable guidance for developing better learning strategies in the future.